Implementation research in health: a practical guide - Peters, David; Tran, Nhan; Adam, Taghreed (World Health Organization, 2013)
Interest in implementation research is growing, largely in recognition of the contribution it can make to maximizing the beneficial impact o f health interventions. As a relatively new and, until recently, rathe r neglected field within the health sector, implementation research is something of an unknown quantity for many. There is therefore a need for greater clarity about what exactly implementation research is, and what it can offer. This Guide is designed to provide that clarity. In tended to support those conducting implementation research, those with responsibility for implementing programs, and those who have an inter est in both, the Guide provides an introduction to basic implementatio n research concepts and language, briefly outlines what it involves, a nd describes the many opportunities that it presents. The main aim of the Guide is to boost implementation research capacity as well as dema nd for implementation research that is aligned with need, and that is of particular relevance to health systems in low- and middle-income co untries (LMICs). Research on implementation requires the engagement of diverse stakeholders and multiple disciplines in order to address the complex implementation challenges they face. For this reason, the Gui de is intended for a variety of actors who contribute to and/or are im pacted by implementation research. This includes the decision-makers r esponsible for designing policies and managing programs whose decision s shape implementation and scale-up processes, as well as the practiti oners and front-line workers who ultimately implement these decisions along with researchers from different disciplines who bring expertise in systematically collecting and analyzing information to inform imple mentation questions. The opening chapters (1-4) make the case for why implementation research is important to decision-making. They offer a workable definition of implementation research and illustrate the rele vance of research to problems that are often considered to be simply a dministrative and provide examples of how such problems can be framed as implementation research questions. The early chapters also deal wit h the conduct of implementation research, emphasizing the importance o f collaboration and discussing the role of implementers in the plannin g and designing of studies, the collection and analysis of data, as we ll as in the dissemination and use of results. The second half of the Guide (5-7) detail the various methods and study designs that can be u sed to carry out implementation research, and, using examples, illustr ates the application of quantitative, qualitative, and mixed-method de signs to answer complex questions related to implementation and scale- up. It offers guidance on conceptualizing an implementation research s tudy from the identification of the problem, development of research q uestions, identification of implementation outcomes and variables, as well as the selection of the study design and methods while also addre ssing important questions of rigor.
Keywords: Delivery of Health Care; Health Plan Implementation; Health Policy; Health Services Research; Research Design; standards